Modern Stents: Where Are We Going? - Kobo, Ofer (Rambam Maimonides Med J, 2020)
Coronary artery stenting is the treatment of choice for patients requiring coronary angioplasty. We describe the major advancements with this technology. There have been significant developments in the design of stents and adjunctive medical therapies. Newer-generation drug-eluting stents (DES) have almost negligible restenosis rates and, when combined with proper anti-platelet treatment and optimal deployment, a low risk of stent thrombosis. The introduction of newer-generation DES with thinner stent struts, novel durable or biodegradable polymer coatings, and new antiproliferative agents has further improved the safety profile of early-generation DES. In parallel the effectiveness has been kept, with a significant reduction in the risk of target lesion revascularization compared with the early-generation DES. However, to date, the development of completely bioresorbable vascular scaffolds has failed to achieve further clinical benefits and has been associated with increased thrombosis. Newer-generation DES—including both durable polymer as well as biodegradable polymer—have become the standard of care in all patient and lesion subsets, with excellent long-term results.